2007
DOI: 10.1136/vr.161.9.295
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a live bovine herpesvirus type 1 marker vaccine under field conditions in three countries

Abstract: The performance of a live marker vaccine for bovine herpesvirus type 1 (bhv-1) was studied in the field in three European Union countries with different farming conditions. The progress in the eradication of the virus was followed in a large herd in Germany and one in Italy, and a major serological survey involving 147 farms was conducted in Hungary. Commercial batches of the same vaccine were used in all three studies. The herds were vaccinated according to agreed protocols and the animals' bhv-1 antibody sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 6 publications
4
9
0
Order By: Relevance
“…However, it was not possible to detect the same effect in the male population of the dairy-beef mixed herds. These results are consistent with those obtained in previous field studies that revealed a reduction of virus circulation in cattle herds hyperimmunized with live-virus vaccine 9,12 or an inactivated-virus vaccine. 10 It is not possible to make further comparisons between results of other studies and those of the present study because conclusions of other studies were based on the reproduction ratio 18 calculated for a period of 18 months in studies in which only female cattle > 1 year old were included.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, it was not possible to detect the same effect in the male population of the dairy-beef mixed herds. These results are consistent with those obtained in previous field studies that revealed a reduction of virus circulation in cattle herds hyperimmunized with live-virus vaccine 9,12 or an inactivated-virus vaccine. 10 It is not possible to make further comparisons between results of other studies and those of the present study because conclusions of other studies were based on the reproduction ratio 18 calculated for a period of 18 months in studies in which only female cattle > 1 year old were included.…”
Section: Discussionsupporting
confidence: 83%
“…11 More recently, hyperimmunization protocols that involve the use of live-virus vaccines have been successfully tested in 149 herds, mostly large dairy farms. 12 Although a hyperimmunization protocol that involves the use of sequential administration of live-virus and inactivated-virus vaccines was found to be efficient, 13 it has not been tested in farm settings. Currently, putative risk factors for BHV-1 infection have been estimated via cross-sectional observational studies.…”
mentioning
confidence: 99%
“…The low uptake of vaccine in herds of adult cows will do little to restrict virus circulation among adult or juvenile stock. Vaccination has been demonstrated to effectively reduce seroprevalence if vaccine usage is conducted in a coordinated manner [26]. In addition to those EU member states already officially free of disease, other countries have already achieved regional eradication (France, Germany, UK, Spain and Italy) or are at various stages of herd certification/eradication (Netherlands, Belgium and Poland among others) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Differentiating infected from vaccinating animals (DIVA) strategy. Marker (gE-deleted) vaccines, which are considered safe and efficacious based on both experimental and field data (European Commission, 2000;Dispas et al, 2004Dispas et al, , 2009EFSA, 2006;Makoschey et al, 2007;Ampe et al, 2012), are available and form the basis of a control strategy where initial prevalence is moderate to high. This approach, supplemented by biosecurity measures to address risks of introduction associated with breeding, trade and husbandry activities, can be used to reduce the initial prevalence, with remaining positive animals being culled when prevalence falls to 5%.…”
Section: Control Toolsmentioning
confidence: 99%
“…Parameter 3 -Field protection as reduced morbidity (as reduced susceptibility to infection and/or to disease) All vaccines licensed in Member States must satisfy the requirements of the IBR Monograph of the European Pharmacopoeia (OIE, 2017). Vaccines with DIVA properties are considered safe and efficacious based on data from experimental and field studies (European Commission, 2000;Dispas et al, 2004Dispas et al, , 2009EFSA, 2006;Makoschey et al, 2007;Ampe et al, 2012). Ultimately their efficacy in the field has been demonstrated by their incorporation into successful national eradication programmes (Commission Implementing Decision (EU) 2015/250).…”
Section: Effectivenessmentioning
confidence: 99%